Migration, citizenship, and development diasporic membership policies and overseas Indians in the United States - Naujoks, Daniel (New Delhi Oxford University Press, 2013)
This title examines the effects of country-of-origin citizenship on the Indian diaspora in the United States and return migrants in India. It explores how the overseas citizenship of India affects remittances, investment, philanthropy, return migration and political lobbying.
Includes bibliographical references and index.
Keywords: East Indian diaspora; East Indians -- Political activity -- United States; Citizenship -- India; Electronic books; United States -- Emigration and immigration -- Government policy